Performance enhancement in a multilevel inverter fed PTC induction motor drive by optimal voltage vector selection - Himabindu T; A.V. Ravi Teja; G Bhuvaneswari; Bhim Singh (Institute of Advanced Engineering and Science, 2019)
This paper proposes a novel predictive control strategy for a multilevel inverter fed Induction Motor Drive (IMD) with optimal voltage vector selection at every sampling interval. The proposed predictive control strategy, apart from enhancing the dynamic speed and torque responses of the drive, strives to reduce the number of switching transitions by choosing optimal voltage vector, thereby reducing the switching losses significantly. The algorithm put forth here chooses the most suitable switching state among the redundant switching combinations, such that minimum number of switches change their states from the previous switching combination to the present one. This results in perceptible reduction in the switching losses thereby increasing the efficiency of the converter. The proposed Predictive Torque Control (PTC) strategy is modeled and simulated in Matlab/ Simulink environment and the results are reported for a 2-level and 3-level inverter fed IMD configurations. The results demonstrate the effectiveness of the proposed PTC for both 2-level and 3-level inverter fed IMDs.